Application of mesopores copper hexacyanoferrate (II) nanomaterials for cesium adsorption - Nguyễn, Đình Trung (Korean Society of Environmental Engineers, 2024)
Mesopores of copper hexacyanoferrate (II) (M-CuHCF-II) nanomaterials used for the cesium (Cs+) removal were synthesized by the chemical coprecipitation method. M-CuHCF-II has a cubic structure (space group F-43m), a surface area of 12.80 m2/g, and a pore width of about 34.49 nm. At pH=6, the adsorption capacity of Cs+ ions by CuHCF-II reached the maximum within 15 minutes. Langmuir, Redlich–Peterson, and Sips models are suitable to describe the adsorption of Cs+ ions by M-CuHF-II materials. The maximum absorption capacity of M-CuHCF-II was determined at 318 K corresponding to the value of 197.72 mg g-1. The Gibbs free energy change (ΔG°) of Cs+ adsorption process with ranging values from -37.47 to -40.74, and ΔH0 = -8.28 (kJ mol-1) at temperatures from 298–348 K. Na+, NH4+, Ca2+, and K+ ions in solution affect the removal of Cs+ ions when they occur at high concentrations. M-CuHCF-II materials are easy to prepare, low-cost, have high adsorption capacity for Cs+ ions, and are easy to apply. In addition, the adsorption mechanism of Cs+ ions by M-CuHCF-II is also proposed and discussed.